2018
DOI: 10.22373/equality.v4i2.4531
|View full text |Cite
|
Sign up to set email alerts
|

English Senior High School Textbook Analysis: Addressing Gender Bias Issues

Abstract: Due to the imbalance gender presentation in English Senior High School textbook detected during teaching practice program, the researcher was interested in doing a research about the issue. Students might take much time to learn from textbooks to develop their gender roles at school, therefore, the proper textbooks which attain the objectives of gender equality are needed. The aim of this study is to investigate whether or not female and male are presented equally in the English Senior High School textbook. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our finding imply to be consistent with other study which found English secondary textbook have demonstrated equality on the basis of quality, visibility and activity. This is exemplified in the study undertaken by Nashriyah and Khairul (2018). They examine the existence of gender bias based on five classifications such as visibility, firstness, masculine generic construction, activity, and occupation.…”
Section: Promotion Of Gendermentioning
confidence: 99%
“…Our finding imply to be consistent with other study which found English secondary textbook have demonstrated equality on the basis of quality, visibility and activity. This is exemplified in the study undertaken by Nashriyah and Khairul (2018). They examine the existence of gender bias based on five classifications such as visibility, firstness, masculine generic construction, activity, and occupation.…”
Section: Promotion Of Gendermentioning
confidence: 99%
“…Amerian and Esmaili (2015) explored the representation of gender in EFL textbooks and found certain degree of sexist attitudes. Nashriyah and Khairul (2018) investigated whether women and men were presented equally in English textbooks in Indonesia and the results showed that women were more visible than men, who nevertheless were dominant in terms of quantity, firstness, and masculine generic construction.…”
Section: Introductionmentioning
confidence: 99%